«Il più efficace cooperatore dei negozi diplomatici»? Adelaide Ristori e il conte Cavour - Paoletti, Matteo (Drammaturgia, 2023)
In April 1861, just one month after the proclamation of the Unification of Italy, Prime Minister Cavour defined Adelaide Ristori «the most effective co-operator of diplomatic negotiations», praising her work at the court of the Czar in the winter of 1860. The letter is well-known since the 19th century and has been the key for creating the myth of the Grande Attore as a tool for cultural diplomacy. During her career, Ristori undoubtedly fascinated international audiences and kings, and thus acted as an effective tool for soft power. However, it is unclear to what extent her action was the result of aware foreign policies by the rising Kingdom of Italy. Drawing upon partially uncharted archival documentation, this essay reconstructs Ristori’s activity at the court of Alexander II, framing her Russian tour in the turbulent context of the Russian-Sardinian relations in the aftermath of Garibaldi’s expedition. In fact, Ristori left for Saint Petersburg during a diplomatic crisis: the Czar had recalled his Ambassador in Turin after the Piedmont army had invaded Naples; Cavour had recalled his delegation. The bilateral relationships were interrupted, although theatrical companies kept on moving across borders. Cavour asked Ristori to ‘convert’ the Russian minister of Foreign affairs, Prince Gorčakov: the fascination for the celebrity could sustain Italy’s cause. Between ceremonial and theatre stages, the peculiar affair imposes a new reflection on the relationship between theatre, celebrity, and influence in the 19th century.